Flexible Amorphous GeSn MSM Photodetectors - Firat Yasar; Wenjuan Fan; Zhenqiang Ma (IEEE Photonics Journal)
We demonstrate amorphous Ge0.92Sn0.08 surface illuminated metal–semiconductor–metal (MSM) photodetectors on flexible substrates for visible wavelength. Photodetection at 633 nm is achieved with an I–V response up to 10–4 A for a 2 V bias voltage. Different evaporation rate effects on the amorphous GeSn MSM photodetector are examined. Bending/strain effects on device performance were studied by evaluating the current density versus voltage characteristics. Amorphous GeSn thin film deposition on polyethylene terephthalate flexible substrate and Ni/Au–GeSn–Ni/Au MSM photodetector finger pattern deposition were performed via thermal evaporation. Photocurrent and dark current densities of amorphous GeSn MSM photodetectors were obtained at 1.36 A/cm2 and 0.24 A/cm2, respectively, where the photocurrent to dark current contrast ratio was found to be equal to 5.6. We also examined the evaporation rate, strain, and bending effect.